Propensity to decide on involuntary hospitalisation in primary medical care: Dispositional or situational determinants?. (March 2020) - Morandi, Stéphane; Silva, Benedetta; Bonsack, Charles; Golay, Philippe
Abstract: Background: The incidence of involuntary hospitalisations varies widely among and within countries. One factor that could account for these variations is the local profile of medical doctors deciding on involuntary admissions. The first goal of this study was to test whether to decide on an involuntary hospitalisation was an individual or a situational disposition. The second goal was to explore doctors' characteristics associated with the use of coercion in specific situations. Method: Medical doctors of four French-speaking Swiss cantons with the competence, according to cantonal laws, to decide on an involuntary hospitalisation were invited to take part in an online survey. Respondents were asked whether they would decide on an involuntary hospitalisation or not in seven clinical vignettes. Propensity to decide on involuntary hospitalisation was estimated with a two-parameter logistic item response model and latent class analysis. Univariate logistic regression models were used to test whether individual factors were associated with the use of coercion in each situation. Results: 192 medical doctors completed the online questionnaire. There was near-zero correlation between vignettes: an involuntary hospitalisation decided on by a doctor in one situation was not related to the use of coercion in another. No subgroup was more prone to generally resort to coercion. However, some individual characteristics were related to the use of coercion in specific situations. Conclusions: Medical doctors' propensity to use coercion for mental health problems was better accounted for by situational rather than dispositional factors. Thus, the use of coercion should be examined as a multidimensional concept.